Transforming the Net Present Value for a Comparable One - Illés, Mária (Theory, Methodology, Practice – Review of Business and Management, 2012)
This study examines the nature of net present value. It defines the economic content of the net present value and mathematically proves that definition is correct. This economic content inducts that the net present values are not comparable. The study systematically eliminates the distortion affects. The net present value transforms into a special kind of rate, namely, the modified difference between the factual and the required rate of return. The ranking list according to this transformed net present value corresponds to the list according to the internal rate of return. This is a new cognition and a very important correspondence.